Keluarga adalah Obat: Dukungan Keluarga Jawa terhadap Orang dengan HIV/AIDS (ODHA) di Masa Pandemi COVID-19, Kasus di Yogyakarta - Atik Triratnawati (Universitas Andalas, 2021)
COVID-19 pandemic affects people's lives on all fronts. PLWHA is one of the vulnerable and marginalized communities affected by COVID- 19. They needs the help of families to support their lives who are always faced with physical, mental, social (stigma and discrimination) and economic problems.This article aims to analyze the Javanese families recilience in helping family members who were PLWHA during the COVID- 19 pandemic. Ethnographic research conducted in DIY in 2020 among PLWHAs through online and offline focus group discussion and offline as well as offline interviews of 10 members of PLWHA family.The economic and social fuction of Javanese nuclear family extend to extended family. Among PLWHA believe that the family is a physical and mental remedy for their lives.Not only nuclear family but also extended family assistance in both material and non-material are able to make survival in the COVID-19 pandemic.Although ODHA families are also affected by COVID- 19, but the spirit of gotong royong helps the weak, the compassion between the healthy and the sick continues to build. The COVID-19 pandemic has strengthened the kinship between them. The help provided by the nuclear and extended families to ODHA is positive because it will break the chain of stigma and discrimination. Through family support and assistance to ODHA self-acceptance, quality of life and family acceptance will continue to increase.